Land surface remote sensing in continental hydrology - Baghdadi, Nicolas; Zribi, Mehrez (San Diego : Elsevier ; London : ISTE Press, 2016)
Annotation The continental hydrological cycle is one of the least understood components of the climate system. The understanding of the different processes involved is important in the fields of hydrology and meteorology. In this volume the main applications for continental hydrology are presented, including the characterization of the states of continental surfaces (water state, snow cover, etc.) using active and passive remote sensing, monitoring the Antarctic ice sheet and land water surface heights using radar altimetry, the characterization of redistributions of water masses using the GRACE mission, the potential of GNSS-R technology in hydrology, and remote sensing data assimilation in hydrological models. This book, part of a set of six volumes, has been produced by scientists who are internationally renowned in their fields. It is addressed to students (engineers, Masters, PhD), engineers and scientists, specialists in remote sensing applied to hydrology. Through this pedagogical work, the authors contribute to breaking down the barriers that hinder the use of Earth observation data. Provides clear and concise descriptions of modern remote sensing methodsExplores the most current remote sensing techniques with physical aspects of the measurement (theory) and their applicationsProvides chapters on physical principles, measurement, and data processing for each technique describedDescribes optical remote sensing technology, including a description of acquisition systems and measurement corrections to be made.
Includes index.
Print version record.
Includes bibliographical references at the end of each chapters and index.
Keywords: Hydrology -- Remote sensing; Hydrological surveys; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Hydrological surveys; Hydrology -- Remote sensing; Electronic books